(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the clinical and paraclinical characteristics of patients with fascioliasis treated at Dang Van Ngu Hospital, Central Institute of Malaria - Parasitology – Entomology. Research subjects and methods: Descriptive study, conducted on 118 patients diagnosed and treated for fascioliasis at Dang Van Ngu Hospital, National Institute of Malaria, Parasitology and Entomology from March 2020 to October 2024. Results: The most common clinical symptoms in patients with fascioliasis were epigastric pain 92.4%, right upper quadrant pain 89.8%, fatigue 51.7%, anorexia 45.8%, diarrhea 31.4%, fever 30.5%. The overall rate of fascioliasis patients with eosinophilia was 73.7%, and the rate of fecal fascioliasis eggs detected was 42.4%. Liver lesions on ultrasound was found in 96.6% of patients with fascioliasis, mainly 1 lesion (45.9%), followed by 2 lesions (35.8%), and 3 or more lesions (18.3%). The most common type of lesion was hete echogenic, accounting for 47.7%. Conclusion: The clinical and paraclinical characteristics of patients with fascioliasis are very diverse. Diagnosis must be based on a combination of clinical characteristics, eosinophilia, and ultrasound images.